Resistance, Continuity, and Change: The New Politics of Pension Reforms in English-Speaking Sub-Saharan Africa. - Kpessa, Michael Whyte (My University, 2009)
Pension reform has been on the social policy agenda in many countries across the world since the 1980s. The main debate has been whether to maintain the postwar PayAs-Y ou-Go (PA YG) pension programs or replace them with private pensions known as individual accounts. lnstitutionalists claim that (PA YG) pension programs are impossible to transform because they are not only fraught with interest group conflicts that have adverse implications for the electoral chances of reform-minded politicians, but also because they are popular among voters, and supported by beneficiaries and trade unions. On the other hand, those international political economists studying welfare reforms argue that the structural transformation of PA YG pension systems is possible and driven by a coalition of global policy actors led by the World Bank. Most of the data that informed these theoretical postulations came from OECD and middle-income countries in Latin America and Eastern Europe. The story of pension reforms in Sub-Saharan African (SSA) countries had until now not been factored adequately into the debate.
This thesis argues that an understanding of pension reforms in SSA countries requires an analysis of both the domestic and international political processes. But this understanding is only possible if the relative role played by domestic and international factors are taken into account and analyzed. Using pension reforms in Ghana since the 1980s as an illustrative case which can inform us about other English-speaking SSA countries, this thesis therefore takes the international level into account, but focuses on the domestic level and argues that domestic politics mattered much more than is assumed by some international political economists in the literature. The thesis affirms aspects of institutionalist arguments, but presents an alternative explanation of pension reforms in SSA that (a) for the first time analyzes the domestic politics of pension reform and (b) casts serious doubts on arguments about the dominant role of transnational actors, while suggests significant improvements to theoretical understandings of pension reform policy processes.
Keywords: political science, Africa, pension, reform